Effect of Flux Application on Aluminium-Silicon Alloy (Al-SiMg) Machining Chips for In-Situ Casting Process - Saleh, Aslinda; Azmi, Azuliana Azwin; Samian, Ain Zubaidah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The primary material used in this study is aluminium-silicon alloy (Al-Si7Mg) machining chips and salt flux. The Al-Si7Mg machining chips were gained by cutting the cylindrical of Al-Si7Mg by using the conventional milling machine to get the chips used in this case study. Generally, machining chips are a waste that comes from machining aluminium pieces in the industries or any machining factories. This study is focusing on the effect of on Al-Si7Mg machining chips for in-situ casting process with the application of equimolar mixtures of salt fluxes sodium chloride (NaCl) and potassium chlorides (KCl). The Al-Si7Mg machining chips was mixed with NaCl-KCl flux for in-situ casting experiment at the temperature of 650oC and 700oC for 30mins. Visual evaluation and Scanning Electron Microscope (SEM) with Energy Dispersive Spectroscopy (EDS) were used for analysis of raw and heated samples. The morphology of the heated AlSi7Mg machining chips were wrinkles with oxide nodules scattering on the surface. EDS result revealed amount of aluminium (Al) element of the heated sample reduced from 91.78 wt. % to less than half proving the chips encountered oxidation during in-situ casting experiment. The fluxes promoted partially melting of the machining chips as the agglomeration of the heated machining chips was developed in the ceramic investment casting mould despite of oxidation.